Serotonergic afferents from the dorsal raphe decrease the excitability of pyramidal neurons in the anterior piriform cortex - Wang, Dejuan (Proc Natl Acad Sci U S A, 2020)
The olfactory system receives extensive serotonergic inputs from the dorsal raphe, a nucleus involved in control of behavior, regulation of mood, and modulation of sensory processing. Although many studies have investigated how serotonin modulates the olfactory bulb, few have focused on the anterior piriform cortex (aPC), a region important for olfactory learning and encoding of odor identity and intensity. Specifically, the mechanism and functional significance of serotonergic modulation of the aPC remain largely unknown. Here we used pharmacologic, optogenetic, and fiber photometry techniques to examine the serotonergic modulation of neural activity in the aPC in vitro and in vivo. We found that serotonin (5-HT) reduces the excitability of pyramidal neurons directly via 5-HT(2C) receptors, phospholipase C, and calcium-activated potassium (BK) channels. Furthermore, endogenous serotonin attenuates odor-evoked calcium responses in aPC pyramidal neurons. These findings identify the mechanism underlying serotonergic modulation of the aPC and shed light on its potential role.